Pengembangan Alat Peraga Fisika Berbasis Internet of Things untuk Praktikum Hukum Newton II - Fayakun Muchlis; Dwi Sulisworo; Moh Toifur (Jurnal Pendidikan Fisika, 2018)
The research purpose is create a physics props of Newton’s Second Law based on internet of things (IoT).The product consists of slippery and rough flat field, photogate sensors, control system box, audio cable, and NewtonApp application. The result shown that developed physics props got very good and feasible appraisal according to all experts.